Retrievals of high latitude surface emissivity across the infrared from high altitude aircraft flights - Murray,JE; Brindley,HE; Fox,S; Bellisario,C; Pickering,JC; Fox,C; Harlow,C; Smith,M; Anderson,D; Huang,X; Chen,X; Last,A; et al. (Journal of Geophysical Research: Atmospheres, 2020)
We present retrievals of infrared spectral surface emissivities spanning the far and mid infrared from aircraft observations over Greenland, taken at an altitude of 9.2 km above sea level. We describe the flight campaign, available measurements and the retrieval method. The principal barriers to reducing uncertainty in the emissivity retrievals are found to be instrumental noise and our ability to simultaneously retrieve the underlying surface temperature. However, our results indicate that using the instrumentation available to us it is possible to retrieve emissivities from altitude with an uncertainty of ~ 0.02 or better across much of the infrared. They confirm that the farinfrared emissivity of snow and ice surfaces can depart substantially from unity, reaching values as low as 0.9 between 400450 cm1. They also show good consistency with retrievals from the same flight made from nearsurface observations giving confidence in the methodology used and the results obtained for this more challenging viewing configuration. To the best of our knowledge, this is the first time that farinfrared surface emissivity has been retrieved from altitude and demonstrates that the methodology has the potential to be extended to planned satellite farinfrared missions.